Analisis Faktor yang Mempengaruhi Niat Konsumen Mengadopsi E-Wallet - Budiman, Johny; Lie, Kelvin; Melvin, Melvin; Halim, Rynando Sadrakh (Universitas Multi Data Palembang, 2024)
The development of sophisticated technology has a very broad effect on various fields, one of which is the financial sector. Fintech can change a person's behavioral intentions in making decisions. There are several objectives from the research results which show factors that have an influence on consumer intention variables in adopting e-wallets in Batam City. Several factors such as performance expectancy, effort expectancy, and perceived enjoyment are considered to have an influence on the behavioral intention variable in adopting e-wallet. The sample in this research is primary data obtained through a questionnaire. The analytical method used in this research is the multiple linear analysis method with the SPSS application. The research results show that there is a significant relationship between performance expectancy and effort expectancy and behavioral intention. Meanwhile, the perceived enjoyment variable does not have a significant relationship with behavioral intention.